The Physicochemical Properties of Deposited Sediments at the Maruba Dam Reservoir Inlet, Machakos County, Kenya - Allois Luvai; John Obiero; Christian Omuto (Applied and Environmental Soil Science)
Energy and water are the two most important natural resources in the globe. In this regard, dams and reservoirs are the critical hydraulic structures that store water and, above all, provide energy required by humanity. However, water storage and the provision of energy by reservoirs and dams have been disrupted by significant environmental changes taking place in the catchment areas and the reservoir environment. These disruptions are brought about by climatic parameters and sediment transport by different eroding agents. One such environmental problem is soil erosion, whose effect is reservoir sedimentation. Consequently, a part of the transported sediment is deposited at the catchment outlet, which serves as the reservoir inlet. This study was carried out to establish the physicochemical characteristics of the deposited sediment at the reservoir inlet. The following parameters were analyzed: particle size distribution, organic matter content, bulk density, porosity, electrical conductivity, penetration resistance, hydraulic conductivity, pH, and nutrients (nitrogen, phosphorous, and potassium) using standard laboratory procedures. The study established that the deposited sediments were predominantly sand particles with mean values of 50.60% and 58.60% for the surface (0–10 cm) or sub-surface horizons (10–20 cm), respectively. The average values for sediment pH, organic matter, porosity, bulk density, electrical conductivity, penetration resistance, hydraulic conductivity, and nutrients were 6.30 and 6.61; 1.91 and 1.80%; 54.10 and 57.10%; 1.22 and 1.14 g·cm−3 for the surface and sub-surface horizons, respectively. The most variable parameters were silt content (sub-surface horizon), hydraulic conductivity, penetration resistance, electrical conductivity, nitrogen content (surface horizon), and phosphorous (surface horizon) content with CV >0.35. Based on the present study results, the deposited sediments at the reservoir inlet were found to have low concentrations of nutrients and high sand proportions. Therefore, the deposited sediments appear to have great potential to reclaim the immediate barren dam environment upon enrichment and to promote sand harvesting programs for economic benefits.